Preparing linked population data for research: cohort study of prisoner perinatal health outcomes. Issue 1 (December 2016) - Hilder, Lisa; Walker, Jane; Levy, Michael; Sullivan, Elizabeth
Abstract Background A study of pregnancy outcomes related to pregnancy in prison in New South Wales, Australia, designed a two stage linkage to add maternal history of incarceration and serious mental health morbidity, neonatal hospital admission and infant congenital anomaly diagnosis to birth data. Linkage was performed by a dedicated state-wide data linkage authority. This paper describes use of the linked data to determine pregnancy prison exposure pregnancy for a representative population of mothers. Methods Researchers assessed the quality of linked records; resolved multiple-matched identities; transformed event-based incarceration records into person-based prisoner records and birth records into maternity records. Inconsistent or incomplete records were censored. Interrogation of the temporal relationships of all incarceration periods from the prisoner record with pregnancies from birth records identified prisoner maternities. Interrogation of maternities for each mother distinguished prisoner mothers who were incarcerated during pregnancy, from prisoner control mothers with pregnancies wholly in the community and a subset of prisoner mothers with maternities both types of maternity. Standard descriptive statistics are used to provide population prevalence of exposures and compare data quality across study populations stratified by mental health morbidity. Results Women incarcerated between 1998 and 2006 accounted for less than 1 % of the 404, 000 women who gave birth in NSW between 2000 and 2006, while women with serious mental health morbidity accounted for 7 % overall and 68 % of prisoners. Rates of false positive linkage were within the predicted limits set by the linkage authority for non-prisoners, but were tenfold higher among prisoners (RR 9.9; 95%CI 8.2, 11.9) and twice as high for women with serious mental health morbidity (RR 2.2; 95%CI 1.9, 2.6). This case series of 597 maternities for 558 prisoners pregnant while in prison (of whom 128 gave birth in prison); and 2, 031 contemporaneous prisoner control mothers is one of the largest available. Conclusions Record linkage, properly applied, offers the opportunity to extend knowledge about vulnerable populations not amenable to standard ascertainment. Dedicated linkage authorities now provide linked data for research. The data are not research ready. Perinatal exposures are time-critical and require expert processing to prepare the data for research.